Revenge of the liar : new essays on the paradox - Beall, J. C. (New York : Oxford University Press, 2007)
Fourteen new essays by some of the world's leading experts, together with an extensive introduction, examine the nature of the Liar paradox and its resistance to any attempt to solve it. - ;The Liar paradox raises foundational questions about logic, language, and truth (and semantic notions in general). A simple Liar sentence like 'This sentence is false' appears to be both true and false if it is either true or false. For if the sentence is true, then what it says is the case; but what it says is that it is false, hence it must be false. On the other hand, if the statement is false, then it i.
Prolegomenon to future revenge / J.C. Beall -- Embracing revenge: on the indefinite extendibility of language / Roy T. Cook -- The liar paradox, expressibility, possible languages / Matti Eklund -- Solving the paradoxes, escaping revenge / Hartry Field -- Validity, paradox, and the ideal of deductive logic / Thomas Hofweber -- On the metatheory of Field's 'Solving the paradoxes, escaping revenge' / Hannes Leitgeb -- Reducing revenge to discomfort / Tim Maudlin -- Understanding the liar / Douglas Patterson -- Revenge, Field, and ZF / Graham Priest -- Field on revenge / Agustín Rayo and P.D. Welch -- Bradwardine's revenge / Stephen Read -- Curry's revenge: the costs of non-classical solutions to the paradoxes of self-reference / Greg Restall -- Alethic vengeance / Kevin Scharp -- Burali-Forti's revenge / Stewart Shapiro -- Revenge and context / Keith Simmons.
Includes bibliographical references and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
English.
digitized
Keywords: Liar paradox; PHILOSOPHY -- Logic; Electronic books; Electronic books